High sensitivity of iPSC-derived motor neurons to the human-relevant botulinum neurotoxin serotypes E and F - Maren Schenke; Alice Westphal; Jasmin Weisemann; Andreas Rummel; Brigitte G. Dorner; Frank Klawonn; Bettina Seeger (NeuroToxicology, 2026)

Design of Novel Fusion Receptor Proteins to Enable Specific Binding of Botulinum Neurotoxins in a Native-like Membrane Environment - Urs von der Kammer; Laura-Varenne Wilk; Adina Przykopanski; Stefan Mahrhold; Brigitte G. Dorner; Andreas Rummel (Toxicon, 2026)

Assembly of Medium Progenitor Toxin Complexes and HA Complexes Into a Large Botulinum Neurotoxin Complex - Andreas Rummel; Kwok-ho Lam; Linfeng Gao; Adina Przykopanski; Baohua Chen; Ting Huang; Maren Krüger; Anna-Magdalena Bartels; Martin Bernhard Dorner; Kay Perry; Brigitte Gertrud Dorner; Rongsheng Jin (Toxicon, 2026)

Mimicking the Multivalent Binding of Bacterial Protein Toxins to Their Cellular Receptors in a Native-Like Membrane Environment - Laura-Varenne Wilk; Urs von der Kammer; Adina Przykopanski; Brigitte G. Dorner; Andreas Rummel (Toxicon, 2024)

An Endopeptidase Suspension Immunoassay for the Detection of BoNT-A and -B in Botulism Patient Sera - Maximilian Steinberg; Laura Wilk; Andreas Rummel; Martin B. Dorner; Brigitte G. Dorner (Toxicon, 2024)

Effects of the North Pacific Current on the productivity of 163 Pacific salmon stocks - Michael J. Malick; Sean P. Cox; Franz J. Mueter; Brigitte Dorner; Randall M. Peterman (Fisheries Oceanography, 2017)
Horizontal ocean transport can influence the dynamics of higher‐trophic‐level species in coastal ecosystems by altering either physical oceanographic conditions or the advection of food resources into coastal areas. In this study, we investigated whether variability in two North Pacific Current (NPC) indices was associated with changes in productivity of North American Pacific salmon stocks. Specifically, we used Bayesian hierarchical models to estimate the effects of the north‐south location of the NPC bifurcation (BI) and the NPC strength, indexed by the North Pacific Gyre Oscillation (NPGO), on the productivity of 163 pink, chum, and sockeye salmon stocks. We found that for salmon stocks located in Washington (WA) and British Columbia (BC), both the BI and NPGO had significant positive effects on productivity, indicating that a northward‐shifted bifurcation and a stronger NPC are associated with increased salmon productivity. For the WA and BC regions, the estimated NPGO effect was over two times larger than the BI effect for pink and chum salmon, whereas for sockeye salmon the BI effect was 2.4 times higher than the NPGO. In contrast to WA and BC stocks, we found weak effects of both horizontal ocean transport processes on the productivity of salmon stocks in Alaska. Our results indicated that horizontal transport pathways might strongly influence population dynamics of Pacific salmon in the southern part of their North American ranges, but not the northern part, suggesting that different environmental pathways may underlie changes in salmon productivity in northern and southern areas for the species under consideration.